2013
DOI: 10.1088/2041-8205/772/1/l8
|View full text |Cite
|
Sign up to set email alerts
|

DETERMINING THE LUMINOSITY FUNCTION OF SWIFT LONG GAMMA-RAY BURSTS WITH PSEUDO-REDSHIFTS

Abstract: The determination of the luminosity function (LF) of gamma-ray bursts (GRBs) is an important role for the cosmological applications of the GRBs, which, however, is seriously hindered by some selection effects due to redshift measurements. In order to avoid these selection effects, we suggest calculating pseudo-redshifts for Swift GRBs according to the empirical L-E p relationship. Here, such a L-E p relationship is determined by reconciling the distributions of pseudo-and real redshifts of redshift-known GRBs.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 45 publications
0
19
1
Order By: Relevance
“…Measuring the L z log log 1 -( ) + distribution by assuming that the GRB rate follows the SFR, Salvaterra et al (2012) reported k 2.3 0.6 b =  or strong comic evolution in GRB number density with a selected redshift-known sample of 52 Swift/BAT GRBs. Employing the L E p -relation to estimate the redshifts for a sample of 498 BAT GRBs, Tan et al (2013) obtained k 2 b~. The derived k and k b values from our analysis are systematically smaller than previous results by these authors.…”
Section: Conclusion and Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Measuring the L z log log 1 -( ) + distribution by assuming that the GRB rate follows the SFR, Salvaterra et al (2012) reported k 2.3 0.6 b =  or strong comic evolution in GRB number density with a selected redshift-known sample of 52 Swift/BAT GRBs. Employing the L E p -relation to estimate the redshifts for a sample of 498 BAT GRBs, Tan et al (2013) obtained k 2 b~. The derived k and k b values from our analysis are systematically smaller than previous results by these authors.…”
Section: Conclusion and Discussioncontrasting
confidence: 57%
“…papers have no redshift information available (e.g., LloydRonning et al 2002;Yonetoku et al 2004;Kocevski & Liang 2006;Tan et al 2013) or have a small size or are collected from GRB surveys with instruments in different energy bands (e.g., Salvaterra et al 2012;Petrosian et al 2009). Before the Swift mission era, the large and uniform sample observed with the Burst and Transient Source Experiment(BATSE) on board theCompton Gamma-Ray Observatory(CGRO) is used for analysis.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlations associated with GRBs have also been used to constrain the cosmological parameters (see Wang et al 2015, for a recent review). The relations between redshifts and other quantities have been used to derive the pseudo-redshift of GRBs (Wei & Gao 2003), and the pseudo-redshifts are used to derive the luminosity function (Tan et al 2013). The fundamental plane relation (Djorgovski & Davis 1987) is used to get the peculiar velocity (Colless et al 2001).…”
mentioning
confidence: 99%
“…where C is a constant and γ is the observed spectral index in energy; see [5] for more details. The corrected luminosity is therefore:…”
Section: Observed Luminositymentioning
confidence: 99%